2003
DOI: 10.1017/s0376892903000031
|View full text |Cite
|
Sign up to set email alerts
|

The incidental ecotourist: measuring visitor impacts on endangered howler monkeys at a Belizean archaeological site

Abstract: Conservationists are missing opportunities to protect species at mass tourism sites where wildlife itself is not the main tourist attraction. At such locations are ‘incidental ecotourists’, i.e. tourists with multiple interests who encounter wildlife or fragile ecosystems inadvertently. A case study from Lamanai Archaeological Reserve, Belize, reveals the motivations of incidental ecotourists and their impact on an endangered primate species, the black howler monkey, Alouatta pigra. Four hundred and seventy-on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
51
1
10

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(74 citation statements)
references
References 31 publications
(36 reference statements)
5
51
1
10
Order By: Relevance
“…Similarly high levels of satisfaction have been recorded at other wildlife viewing destinations in New Zealand (Schanzel & Mcintosh, 2000), Australia (Orams, 2000;Valentine et al, 2004), and Belize (Grossberg et al, 2003). General measures of satisfaction typically receive uniformly high ratings (Herrick & McDonald, 1992), so these results are not surprising.…”
Section: Overall Visitor Satisfactionsupporting
confidence: 54%
See 1 more Smart Citation
“…Similarly high levels of satisfaction have been recorded at other wildlife viewing destinations in New Zealand (Schanzel & Mcintosh, 2000), Australia (Orams, 2000;Valentine et al, 2004), and Belize (Grossberg et al, 2003). General measures of satisfaction typically receive uniformly high ratings (Herrick & McDonald, 1992), so these results are not surprising.…”
Section: Overall Visitor Satisfactionsupporting
confidence: 54%
“…In Finland most people perceived a low negative impact of fishing on Saimaa ringed seals, even though local biologists considered the species at risk due in part to hunting and fishing (Tonder & Jurvelius, 2004). Similar results were found in Belize where only 18% of tourists who witnessed negative interactions with howler monkeys perceived them as being harmful (Grossberg et al, 2003). Low incidence of statements regarding tourism's negative impacts may be related to perceptions of wellrun trips with good environmental management (Cessford & Dingwall, 1994) Other research has demonstrated an inverse relationship between tourist level of education and perceptions of impact (Deng et al, 2003, Grossberg et al, 2003).…”
supporting
confidence: 57%
“…This questioning includes investigating exaggerated claims about ecotourism, and interrogating assumptions made about ecotourists (Shepherd 2002;Butcher 2003;Grossberg et al 2003). There is also a greater realisation that ecotourists are complex individuals who often defy tourist typologies, and have various motivations and interests, and are of different behaviour types (McMinn & Cater 1998).…”
Section: Relevant Literature Ecotourism Versus Mass Tourism: Is Therementioning
confidence: 99%
“…Mixed-methods surveying is common in tourist perception studies; surveys typically include closed questions about demographics, and less structured questions about motivations, expectations and perceptions, related likes/dislikes and reasons for them (examples: Hvenegaard & Dearden 1998;Gnoth 1999;Farrell & Marion 2001;Hillery et al 2001;da Silva 2002;Grossberg, Treves et al 2003;Luck 2003;Kuvan & Akan 2005;Mohsin 2005). …”
Section: Survey Design Sampling and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation